Kinematics of spinal motion during prolonged rowing - Holt, P. J. E.; Bull, A. M. J.; Cashman, P. M. M. (International Journal of Sports Medicine, 2003)
Low back pain is a common problem in rowers of all levels. Few studies have looked at the relationship between rowing technique, the forces generated during the rowing stroke and the kinematics of spinal motion. Of particular concern with respect to spinal injury and damage are the effects of fatigue during long rowing sessions. A technique has been developed using an electromagnetic motion system and strain gauge instrumented load cell to measure spinal and pelvic motion and force generated at the handle during rowing on an exercise rowing ergometer. Using this technique 13 elite national and international oarsmen (mean age 22.43 +/- 1.5 y) from local top squad rowing teams were investigated. The test protocol consisted of a one hour rowing piece. During this session rowing stroke profiles were quantified in terms of lumbopelvic kinematics and stroke force profiles. These profiles were sampled at the start of the session and at quarterly intervals during the hour piece. From this data we were able to quantify the motion of the lumbar spine and pelvis during rowing and relate this to the stroke force profile. The stroke profiles over the one hour piece were then compared to examine the effects of prolonged rowing. This revealed marked increases in the amount of spinal motion during the hour piece. The relevance of this with regard to low back pain requires further investigation.